The Relationship Between Social Identity and Individual Involvement in the Community Toward a Sense of Community: My Day Indonesia at the Day6 Forever Young 2025 Jakarta Concert - Zakiyah Aulia Sabrina Hanifah Jauhary; Rifqi Farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This research investigates the psychosocial dynamics within the My day Indonesia fan community of Day6 triggered by widespread dissatisfaction with the